Effects of a 24-week multicomponent training program on functional capacity, persistent symptoms, body composition, and physical activity in patients significantly affected by COVID-19: the COVID-19 and REhabilitation study (CORE-study)—randomized clinical trial - Danielevicz, Angelica; Diesel, Mabel; dos Santos, Carla Elane Silva; Sirydakis, Maria Eduarda de Moraes; de Melo, Paulo Urubatan Gama; Constantini, Marina Isolde; Hansen, Fernanda; Gerage, Aline Mendes; Freitas, Cintia de la Rocha; Rech, Cassiano Ricardo; Fonseca, Fernanda Rodrigues; Maurici, Rosemeri; et al. (Frontiers in Sports and Active Living, 2025)
BackgroundCOVID-19 can lead to reduced functional capacity, loss of muscle mass, and lasting and persistent symptoms, resulting in reduced physical activity.ObjectiveTo evaluate the effects of a multicomponent training on functional capacity, persistent symptoms, body composition, pulmonary function, and physical activity levels in patients significantly impaired by SARS-CoV-2.MethodsThe participants were randomly assigned (1:1) to either the intervention group (IG), which received multicomponent training (balance/aerobic/resistance), or the control group (CG). Functional capacity [6 min walk test (6MWT)—primary outcome, sit and reach, sit-to-stand, timed up and go], persistent symptoms (dyspnea, fatigue, post-COVID functional status, frailty), body composition (dual-energy x-ray absorptiometry and bioimpedance), pulmonary function, and physical activity levels (accelerometry) were evaluated at baseline and after 24 weeks. Generalized estimating equations were used, with the significance level set at α = 0.05. Outcomes were analyzed by intention-to-treat (ITT) and per-protocol (PP) approaches. Effect sizes were calculated from the mean difference between groups of changes between pre- and post-intervention.ResultsForty participants [age = 52.00 (12.93) years, 19 women] were included. The primary outcome 6MWT showed improvement in both groups in the ITT analysis (IG: 35.5 m, 95% CI: −3.0 to 74.1; CG: 37.4 m, 95% CI: −5.26 to 80.2) and in the IG (87.6 m, 95% CI: 50.6–124.4) in the PP analysis. The IG showed a reduction in mental fatigue (−1.7 points, 95% CI: −0.5 to 3.5) and general fatigue (−6.5 points, 95% CI: −9.4 to −3.5) in our ITT analysis. The IG also revealed improvement in timed up and go test (−1.6 s, 95% CI: −2.6 to −0.6), mental fatigue (−2.0points, 95% CI: −3.6 to 0.7), general fatigue (−6.4points, 95% CI: −11.0 to −1.6), and a protective effect against increased body fat in PP analysis.ConclusionThis program was effective in improving fatigue in patients previously significantly affected by COVID-19.